The solution of an open problem given by H. Haruki and T. M. Rassias. (1999) - Kim, Bara
Abstract : Haruki and Rassias [1] generalized the Poisson kernel in two dimensions and discussed integral formulas for each case. They presented an open problem for an integral formula. In this paper, we give a solution to that problem.